2010
DOI: 10.1186/1471-2164-11-343
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the cardiomyocyte transcriptome vs translatome by endothelin-1 and insulin: translational regulation of 5' terminal oligopyrimidine tract (TOP) mRNAs by insulin

Abstract: BackgroundChanges in cellular phenotype result from underlying changes in mRNA transcription and translation. Endothelin-1 stimulates cardiomyocyte hypertrophy with associated changes in mRNA/protein expression and an increase in the rate of protein synthesis. Insulin also increases the rate of translation but does not promote overt cardiomyocyte hypertrophy. One mechanism of translational regulation is through 5' terminal oligopyrimidine tracts (TOPs) that, in response to growth stimuli, promote mRNA recruitm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…Hence, most of the mRNA transcribed from IEG appeared also translated in response to ET1. However, 17% of mRNA were increased to a greater extent in the polysome-associated pool than in the total transcriptome whereas some others were excluded, which is indicative of regulations of the translational machinery by ET1R-induced signaling to promote mRNA-selective translation, as the authors confirmed later ( 23 ).…”
Section: The Scarse Translatomes Of Gpcrsmentioning
confidence: 85%
“…Hence, most of the mRNA transcribed from IEG appeared also translated in response to ET1. However, 17% of mRNA were increased to a greater extent in the polysome-associated pool than in the total transcriptome whereas some others were excluded, which is indicative of regulations of the translational machinery by ET1R-induced signaling to promote mRNA-selective translation, as the authors confirmed later ( 23 ).…”
Section: The Scarse Translatomes Of Gpcrsmentioning
confidence: 85%
“…The translating ribosome affinity purification (TRAP) approach described in vivo by Heiman et.al [4] and Doyle et.al [5] allows for freshly transcribed gene products, contributing directly to protein production and precipitated straight from the polysome, to be recovered from murine CNS cells. Other studies have used similar methods to examine TLT in biological contexts ranging from cardiomyocytes [6] to stress response in yeast [7] and surveys of discrete cellular populations in Arabidopsis [8]. In Markou et.al [6], 5' terminal oligopyrimidine tracts (TOPs) are used to indirectly measure translation levels and comparatively assess the activity of TLT and TST among cardiomyocyte populations.…”
Section: Recovery and Definition Of Fractionated Mrna Poolsmentioning
confidence: 99%
“…Other studies have used similar methods to examine TLT in biological contexts ranging from cardiomyocytes [6] to stress response in yeast [7] and surveys of discrete cellular populations in Arabidopsis [8]. In Markou et.al [6], 5' terminal oligopyrimidine tracts (TOPs) are used to indirectly measure translation levels and comparatively assess the activity of TLT and TST among cardiomyocyte populations. Halbeisen and Gerber [7] observe that TLT of yeast, harvested using polyribosome precipitation and bulk purification of the associated mRNA, acts to coordinate messages observed in TST during stress response.…”
Section: Recovery and Definition Of Fractionated Mrna Poolsmentioning
confidence: 99%
“…It is known that most eukaryotes regulate growth through the TOR-S6K signal transduction pathway, selectively stimulating mobilization of the (r)-protein mRNAs into polysomes for (r)-protein synthesis (Grolleau et al 2002, Hamilton et al 2006, Markou et al 2010). This pathway is activated either by insulin or by members of the insulin-like growth factor family in all organisms, from yeast to mammals (Fingar andBlenis 2004, Leevers andHafen 2004), including plants (Reyes de la Cruz et al 2004, Robaglia et al 2004).…”
Section: The Translational Control Of (R)-protein Expressionmentioning
confidence: 99%